NILAI PENDIDIKAN KARAKTER DALAM KISAH COLLIQ PUJIE - Rayhan Adi Anggara; Salam Salam; Sultan Sultan (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The Value of Character Education in the Story of Colliq Pujie. This study aims to describe the values of character education and the strategy of conveying the values. This research is qualitative descriptive. This research was conducted by reading and recording the values of character education and its delivery strategies. The results of the study found five main values of character education values based on Permendikbud No. 20 of 2018 in the story of Colliq Pujie. In the independent value, a different subvalue was found from the description of Permendikbud No. 20 of 2018, namely, the innovative subvalue. The strategy of conveying the values of character education is conveyed directly through the painting of character and descriptions in events/stories. Strategy indirectly, conveyed through the author's language style and implied in the story. The styles of language found are majas reps and hyperbole.